A bibliometric worldview of breast-conserving surgery for breast cancer from 2013 to 2023 - Cao, Siyang; Wei, Yihao; Huang, Jing; Yue, Yaohang; Deng, Aishi; Zeng, Hui; Wei, Wei (Frontiers in Oncology, 2024)
Over the last decade, significant advancements have been made in breast-conserving surgery (BCS) for breast cancer. However, there is a lack of analytical and descriptive investigations on the trajectory, essential research directions, current research scenario, pivotal investigative focuses, and forthcoming perspectives. The objective of this research is to provide a thorough update on the progress made in BCS for breast cancer over the preceding decade. Retrieved from the Web of Science database, the data span from January 1, 2012, to November 30, 2023. Utilizing a set of sophisticated analytical instruments, we conducted comprehensive bibliometric and visual analyses. The findings underscore the predominant influence of the USA, representing 35.77% of the overall publications and playing a pivotal role in shaping research within this field. Notable productivity was evident at various institutions, including the Memorial Sloan Kettering Cancer Center, the University of Texas MD Anderson Cancer Center, and the University of Toronto. Annals of Surgical Oncology contributed the most publications in this field. An examination of keywords indicated a change in the concentration of research attention, transitioning from molecular subtype, ultrasonography, and intraoperative aspects to SEER, male breast cancer, and adjuvant measures. By offering a comprehensive bibliometric assessment, this study enhances our understanding of BCS for breast cancer. Consequently, this benefits both experienced researchers and newcomers alike, providing prompt access to essential information and fostering the extraction of innovative concepts within this specific field.